A systematic review of pooled procurement of medicines and vaccines: identifying elements of success - Koray Parmaksiz; Elizabeth Pisani; Roland Bal; Maarten Olivier Kok (BMC, 2022)
Abstract Introduction Pooled procurement of health commodities has increasingly been promoted as a solution to reduce prices, increase availability, and achieve more efficient procurement processes. However, little is known about what is required to implement pooled procurement mechanisms successfully and how they function under specific circumstances. Therefore, the aim of this systematic review is to synthesize empirically grounded insights by identifying the elements that are essential for setting up and operating pooled procurement mechanisms of medicines and vaccines. Methods Our review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched PubMed, Scopus and Web of Science for empirical studies on pooled procurement of medicines and vaccines using various search terms. Publications were assessed based on predetermined eligibility criteria. Results Our initial search yielded 1596 publications, of which 44 were eventually included in our review. Most of the included articles focused on pooled procurement mechanisms that operated on a sub-national level (43%), procured a variety of products (38%), and were set up with the goal to contain costs (64%). The review identified several elements that are essential for pooled procurement mechanisms to function. We organized these elements around three key actors in the mechanism: buyers, the pooled procurement organization, and suppliers. To participate in pooled procurement, buyers need a sufficient level of technical capacity, financial capacity and compatible laws and regulations. To carry out pooled procurement, the pooled procurement organization needs sufficient financial capacity, technical capacity, and independent operations. To supply the mechanism with health commodities, suppliers need sufficient incentives, such as a sufficient market size and a prompt payment mechanism. Conclusion Pooled procurement mechanisms are very diverse. They differ in characteristics and organizational structures and are set up to achieve a variety of goals. While certain essential elements are more likely to increase successful implementation and functioning of pooled procurement mechanisms, the organizational structure must be aligned with the goals of the mechanism, and adapted to the local contextual environment.